2008
DOI: 10.1073/pnas.0711113105
|View full text |Cite
|
Sign up to set email alerts
|

Functional integration across a gradient of corticostriatal channels controls UP state transitions in the dorsal striatum

Abstract: Coordinated near-threshold depolarized states in cortical and striatal neurons may contribute to form functionally segregated channels of information processing. Recent anatomical studies have identified pathways that could support spiraling interactions across corticostriatal channels, but a functional outcome of such spiraling remains to be identified. Here, we examined whether plateau depolarizations (UP states) in striatal neurons relate better to active epochs in local field potentials recorded from close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…We avoided the use of ketamine because we had previously observed that this noncompetitive antagonist of NMDA receptors produces a massive change of firing patterns in the SNr of control animals (Villa and Lorenzana, 1997). We have also avoided the use of urethane because of urethane-induced slow wave cortical activity that alters significantly the analysis of correlations between spike trains (Jones, 2004;Kasanetz et al, 2008;Manns et al, 2000a,b). Our finding that IPT and regular spiking neurons were the commonest types of firing under Equithesin anesthesia appears in agreement with recordings performed in the STN of unanesthetized 6-OHDA treated rats that shown also a decrease in the number of oscillatory units (Allers et al, 2000;Kreiss et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…We avoided the use of ketamine because we had previously observed that this noncompetitive antagonist of NMDA receptors produces a massive change of firing patterns in the SNr of control animals (Villa and Lorenzana, 1997). We have also avoided the use of urethane because of urethane-induced slow wave cortical activity that alters significantly the analysis of correlations between spike trains (Jones, 2004;Kasanetz et al, 2008;Manns et al, 2000a,b). Our finding that IPT and regular spiking neurons were the commonest types of firing under Equithesin anesthesia appears in agreement with recordings performed in the STN of unanesthetized 6-OHDA treated rats that shown also a decrease in the number of oscillatory units (Allers et al, 2000;Kreiss et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there appears to be a dual organization that permits both parallel and integrative processing. Thus, the ventral cortico-basal ganglia network, while at the heart of reward processing, does not work in isolation (Belin and Everitt, 2008;Bevan et al, 1997;Brown et al, 1998;Draganski et al, 2008;Haber et al, 2000Haber et al, , 2006Joel and Weiner, 1994;Kasanetz et . Schematic illustrating key structures and pathways of the reward circuit.…”
Section: Reward and The Basal Gangliamentioning
confidence: 99%
“…Under certain conditions, if collectively activated, they may provide the recruitment strength necessary to modulate striatal activity by broadly disseminating cortical information. This relatively low level of modulation may provide an anatomical substrate for cross-encoding information to influence the future firing of medium spiny neurons (Kasanetz et al, 2008), playing an important role in the temporal activation of different striatal regions during learning. Taken together, the fronto-striatal network constitutes a dual system comprising both topographically organized terminal fields and subregions that contain convergent pathways derived from functionally discrete cortical areas (Draganski et al, 2008;Haber et al, 2006).…”
Section: Connections Of the Vsmentioning
confidence: 99%
“…MPFC inputs to the striatum are organized in a dual system: focal projections to subregions of the ventral striatum, specifically to the nucleus accumbens, the medial portion of the caudate, and the ventromedial part of the putamen, which play a role in encoding the relative value and the outcome of chosen options during decisions 47 ; diffuse pathways to the entire striatum that converge with inputs from other PFC areas and regulate the firing of medium spiny neurons, thus modulating temporal activation of different striatal regions during learning. 48 Tracer studies in monkeys 49 and imaging studies 4 have shown that the dorsal caudate is connected with PCC. Intriguingly, pharmacological challenge with DA agonists, and Positron Emission Tomography (PET) studies have shown that DA signaling can modulate the relationship between the DMN and striatal networks both at rest 4 and during the performance of a cognitive task.…”
Section: Drd2 Effects On Default Mode and Striatal Networkmentioning
confidence: 99%